THE EURASIAN ECONOMIC UNION’ BANKING SECTOR INTEGRATION: PROBLEMS AND THE DEVELOPMENT DIRECTIONS - T. Blokhina; A. Gladkaya; A. Kostina (Вестник университета)
Current state of the process of integration of banking systems of the member States of the Eurasian economic Union has considered. Based on the comparison of the main indicators of the banking sector development in the states of the Eurasian Economic Union countries, the main differences in the approaches of the States to the development of national banking systems have highlighted. Nowadays they are currently developing autonomously, despite the steps taken to integrate them has revealed. The SWOT-analysis of the factors influencing the integration in order to identify the positive and negative aspects of this process development has made.